Chapter О некоторых особенностях словоупотребления в поэтическом словаре Достоевского. В связи с книгой М.Л. Уральского и Г. Мондри Достоевский и евреи (Санкт-Петербург: Алетейя, 2021) - Barsht, Konstantin (Biblioteca di Studi Slavistici, 2023)
On Features of Word Usage in Dostoevsky's Poetic Dictionary in Connection with M.L. Uralskij and G. Mondry's Dostoevsky and the Jews (St. Petersburg: Aletheia, 2021) . This article addresses the question of Dostoevsky's alleged anti-Semitism with particular attention to Uralskij and Mondry's book devoted to this topic, in which conclusions about the author's chauvinism and xenophobia are based on his use of the word 'Jew' (zhid). For almost the entirety of the 19th century, however, such word usage was not a marker of anti-Semitism. Throughout his life, Dostoevsky communicated with many representatives of the Jewish people without differentitating them in any particular way from representatives of other nationalities. In the writer's poetic dictionary, the word 'Jew' sometimes denotes a person who acquires unscrupulously, examples of which Dostoevsky found in all nationalities of the world, including the Russian.